THE INFLUENCE OF LABOR, CAPITAL, AND MANAGEMENT ON THE PRODUCTIVITY OF IMKM ASSISTED BY THE DINAS PERINDUSTRIAN DAN PERDAGANGAN KAB. TTU - Desmon Redikson Manane; Natalia Lily Babulu; Maximus Leonardo Taolin (SEAN Institute, 2022)
This study aims to determine the effect of labor, capital, management partially and simultaneously on productivity. The research data used is primary data through questionnaires. The method used is simple and multiple linear regression analysis. The results of this study prove that partially the labor variable, the management variable has a positive and significant effect on increasing productivity, in contrast to the capital variable it has a negative and significant effect on the productivity of micro, small and medium industries (IMKM). This indicates that productivity will increase if: good business planning, prioritizing the quality and quality of the work, adequate work wage planning, gradual strict supervision in production activities, workforce involvement in every education and job training and discipline in work. Meanwhile, simultaneously, the variables of labor, capital and management have a positive and significant effect on productivity. This study proves that these three variables make a significant contribution to increasing business productivity of the micro, small and medium industries (IMKM).